Pengaruh Posisi Pengelasan pada Pengelasan SMAW Material Baja SS400 terhadap Kekuatan Tarik dan Bending Sambungan Las - Kiki Kurniawan; Kosjoko Kosjoko; Rohimatush Shofiyah (Jurnal Kendali Teknik dan Sains, 2025)
Welding is one of the most essential metal joining processes in manufacturing, construction, and industrial applications, where Shielded Metal Arc Welding (SMAW) remains widely used due to its flexibility, cost-effectiveness, and ability to be applied in various welding positions. This study aims to analyze the effect of welding position variations on the mechanical properties of SS400 steel, particularly in terms of tensile strength, bending strength, and microstructural characteristics. The experimental method was conducted using 6 mm thick SS400 steel with E6013 electrodes of 2.6 mm diameter in three welding positions: 1G, 2G, and 3G. The welded specimens were then tested through tensile testing (ASTM E8) and bending testing (ASTM E190-14), followed by microstructural analysis in the weld metal area. The results revealed that welding position significantly affects the mechanical properties of welded joints, where the 3G position produced the highest tensile strength of 188.48 kgf/mm², while the 2G position produced the lowest tensile strength of 113.70 kgf/mm². Conversely, the bending test showed that the 2G position provided the maximum bending strength of 1394 kgf/mm², followed by 3G and 1G positions. Microstructural observations demonstrated variations in the distribution of ferrite, pearlite, martensite, and cementite phases across different welding positions, with the dominance of ferrite and pearlite in the 3G specimen contributing to higher tensile strength, while the dominance of martensite and cementite in the 2G specimen enhanced hardness and bending resistance. Overall, this study confirms that welding position plays a crucial role in determining the quality of SS400 welded joints, and the findings are expected to serve as practical guidance for industry in selecting appropriate welding positions for construction needs, while encouraging further research with additional variables such as electrode type, welding current, and post-weld heat treatment to achieve a more comprehensive understanding.